Ajustes cardiovasculares em modelo experimental descerebrado, cascavel sul americana (Crotalus durissus) - Tavares, Driele (2021)
The reptile class has considerable importance among vertebrates for investigations about the evolution of modulatory mechanisms in the cardiovascular system. Some cardiovascular studies have been performed with in situ measurements and experimental models under terminal anesthesia. Unfortunately, this approach compromises cardiovascular responses by suppressing autonomic modulations. The present study analyzes the effectiveness of a new experimental model for cardiovascular studies in Squamates using decerebrate animals. The model allows recording several physiological variables on an animal preparation euthanized with a functional autonomic nervous system (ANS), free of anesthetic interferences. For the decerebrate preparation to be considered adequate, several levels of validations are needed that observe: the ANS's ability to recover; the integrity of that system throughout the experimental process; its ability to process and coordinate responses to challenges; its degree of similarity with the intact animal, as well as the functional viability time of the preparation. Thus, we had the following objectives: (1) to evaluate the profile of the progression of post-surgical recovery on the mean values of cardiovascular parameters at rest and its stability over time; (2) to assess the post-surgical recovery level of the autonomic modulation of a complex cardiovascular mechanism, such as the baroreflex; (3) to assess the profile of the progression of autonomic post-surgical recovery, reflected by modulatory indices, such as Heart Rate Variability (HRV) and baroreflex; (4) to evaluate the ANS's responsiveness and adaptation of the hemodynamic regulation of preparations submitted to hemodynamic challenges. We observed that the preparations maintained mean cardiovascular parameters at rest stable and similar to those of intact animals. Furthermore, with the preparation, it was possible to accomplish highly complex instrumentation, record a large number of concomitant parameters and integrate them. Baroreflex indices, representative of complex autonomic modulatory processes, were recovered to the level observed on intact animals at rest three days after surgery. The autonomic modulatory indicators used (baroreflex and HRV) remained stable for at least 15 days. The preparations were able to perform complex hemodynamic adjustments in response to hemodynamic challenges and chemoreceptor stimuli for an extended period after the surgical procedure. The anesthesia procedure changed the profile of modulatory responses to challenges under the same conditions, proving the persistence of autonomic processes. We conclude that the model is representative of the species, as it can maintain the cardiovascular parameters similar to those of intact animals. It is a valuable model because it allows for multiple variables recording. It is viable for long-term procedures, as it maintains these capabilities for a long time after euthanasia.